Paleopathological studies of pre-Columbian populations from Northwestern Argentina - Drube, Hilton (2017)
The general aim of this paper is to present the results of studies in the field of paleopathology, which was conducted on human remains from pre-Hispanic aboriginal settlements located in the Hualfín Valley in the province of Catamarca and in the middle basins of the rivers Dulce and Salado in the province of Santiago del Estero, in northwestern Argentina.